The impact of policies to reduce blood glucose test strip utilization and costs in Canada - Gomes, Tara (Can J Public Health, 2015)
OBJECTIVES: Several strategies have been proposed to manage the utilization of blood glucose test strips (BGTS) in Canada; however their potential impacts on utilization and costs of publically funded test strips are unknown. METHODS: We investigated the impact of three potential policies that would restrict the number of test strips reimbursed by the public drug plans in Ontario and British Columbia (BC), and incorporated negotiated price reductions. These policies were based on recommendations from the Canadian Agency for Drugs and Technologies in Health, a briefing document by the Canadian Diabetes Association, and a new policy introduced by the Ontario Ministry of Health and Long-Term Care. BGTS utilization rates were assessed in two cross-sectional analyses among adults aged 18 years or older in BC and 65 or older in Ontario who received publicly-funded BGTS between January 2004 and December 2012. We modeled the 5-year utilization and cost implications of the three policies using time-series analysis. RESULTS: In 2012, there were 31 7,1 30 test strip recipients in Ontario and 1 36,659 recipients in BC, at a cost of $104.4 million and $22.6 million respectively. Under the scenarios of reduced BGTS quantities, 5-year cost savings ranged between $98.8 million (18.2% reduction) and $224.1 million (41.4% reduction) in Ontario and between $23.1 million (19.2% reduction) and $51.1 million (42.4% reduction) in BC. Price reductions of 15% resulted in annual savings of $14.4 million (1 3.7% reduction) in Ontario and $3.4 million (14.1% reduction) in BC. CONCLUSIONS: Policies that align with evidence and expert guidance could impart substantial cost savings in multiple jurisdictions despite different public drug plans.